Estimation of daily solar radiation at equatorial region of West Africa using a more generalized Angström‑based broadband hybrid model (2020)
A well-calibrated simple and economical viable Ȧngström–Prescott model has long been accepted to be more accurate than other surface meteorological data-based models. The major limitation is that it is site dependent. This study exploited the appropriateness of a more generalized Ȧngström-based broadband hybrid model in the estimation of solar radiation at seven stations in equatorial region of West Africa. This model features parametric equations that explicitly and accurately account for clear-sky damping processes in the atmosphere. It empirically estimates cloudy sky radiation extinctions using relative sunshine duration. A new cloud transmittance calibration curve that followed the cloud cover patterns of the region of study was also tried. The result indicated that the new cloud transmittance could be unique to equatorial region of West Africa. The performance of the hybrid model, after modification using the new cloud transmittance equation, was tested using mean bias error and root mean squared error. The performance was found to be comparable to the site-dependent, locally calibrated, Ȧngström–Prescott model at the calibration stations, and even better at validation stations. The same performance test comparisons with the original version of the hybrid model, and four other site-independent models: globally calibrated, FAO-recommended Ȧngström–Prescott models, Hay and Gopinathan models indicated the modified version of the hybrid model as better